2002
DOI: 10.1097/00042737-200206000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized comparison of omeprazole Multiple Unit Pellet System (MUPS) 20 mg, lansoprazole 30 mg and pantoprazole 40 mg in symptomatic reflux oesophagitis followed by 3 months of omeprazole MUPS maintenance treatment: a Dutch multicentre trial

Abstract: Omeprazole MUPS 20 mg and pantoprazole 40 mg have equivalent efficacy in the treatment of reflux oesophagitis. Based on patient satisfaction, omeprazole MUPS 20 mg, lansoprazole 30 mg and pantoprazole 40 mg are equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Figure 2 shows the flow of this meta‐analysis, listing studies excluded and citing reasons for exclusion. A total of 59 randomized controlled trials met the criteria for inclusion in the meta‐analysis comprising a total of 26 885 patients in active treatment arms (see supplementary Table S1 online) 15,16,24–80 . The studies were published between 1988 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the flow of this meta‐analysis, listing studies excluded and citing reasons for exclusion. A total of 59 randomized controlled trials met the criteria for inclusion in the meta‐analysis comprising a total of 26 885 patients in active treatment arms (see supplementary Table S1 online) 15,16,24–80 . The studies were published between 1988 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…The sub‐classes of randomized controlled trials in the English language were as follows: omeprazole and GERD, 104 trials; omeprazole and ulcer disease, 726 trials; lansoprazole and GERD, 24 trials; lansoprazole and ulcer disease, 193 trials; rabeprazole and GERD, 10 trials; rabeprazole and ulcer disease, 34 trials; pantoprazole and GERD, 11 trials; pantoprazole and ulcer disease, 70 trials; esomeprazole and GERD, 110 trials; esomeprazole and ulcer disease, 496 trials. Of these numerous studies, 36 met our a priori criteria for analysis and/or were relevant to our specific aims and were abstracted 6–41 . On further detailed evaluation during the abstraction process, one of these studies was found to have been carried out without blinding and was excluded, 12 two were found to have a Jadad score of only two and were excluded from further analysis 13 , 29 and one study's primary outcome was based on surrogate end‐points (intra‐oesophageal pH) and was also excluded 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Decrease of symptom scores and the proportion of patients who maintain symptom control were chosen as primary outcomes for the first and second phase of the study, respectively, in order to reflect the characteristics of symptomatic responses to PPI in RE patients. Because treatment with lansoprazole for 4 weeks generally leads to significant symptom relief in responsive patients, it may be less appropriate to consider magnitude of symptom improvement as the study outcome in the second phase [28, 29]. Moreover, after receiving different study medications in the first phase, patients could not be regarded as comparable at entry to the second phase.…”
Section: Discussionmentioning
confidence: 99%